2013
DOI: 10.1590/s0103-166x2013000200014
|View full text |Cite
|
Sign up to set email alerts
|

O profissional de saúde mental na reforma psiquiátrica

Abstract: O objetivo desse artigo é examinar criticamente produções da literatura científica sobre a Reforma Psiquiátrica Brasileira, publicadas entre 2003 e 2011, abordando estudos que focalizaram o trabalhador de saúde mental. A pesquisa organizou-se por meio de leitura sistemática e análise dos artigos, em termos de seus objetivos, metodologia, resultados e conclusão. Foram encontrados 14 artigos, que se revelaram convergentes quanto aos resultados obtidos na medida em que concluem que os trabalhadores manifestam-se … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
15

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 19 publications
1
2
0
15
Order By: Relevance
“…Therefore, according to the young people surveyed, the prejudice against people with mental disorders is a major barrier to accessing heath care services. This result is in accordance with those of Simões et al (2013), who found that changes in policies for mental health services and greater availability of services are insufficient to overcome the prejudice about mental ilness. Identifying stigma as a major barrier faced by young people seeking out mental health treatment demonstrates that there is a lot still to be done in terms of overcoming the discrimination against users of mental health services in Brazil.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Therefore, according to the young people surveyed, the prejudice against people with mental disorders is a major barrier to accessing heath care services. This result is in accordance with those of Simões et al (2013), who found that changes in policies for mental health services and greater availability of services are insufficient to overcome the prejudice about mental ilness. Identifying stigma as a major barrier faced by young people seeking out mental health treatment demonstrates that there is a lot still to be done in terms of overcoming the discrimination against users of mental health services in Brazil.…”
Section: Discussionsupporting
confidence: 91%
“…There is still a lot social prejudice surrounding the mental health care of children and adolescents and other age groups, which is held by the children and adolescentes themselves and is also seen within health. The lack of knowledge in the general public and health professionals about the particularities of mental health care can be identified as a factor that contributes to the stigma associated to mental illness (Simões, Fernandes, & Aiello-Vaisberg, 2013).…”
Section: Barriers To Mental Health Care Accessmentioning
confidence: 99%
“…However, Brazilian psychiatric reform gained strength in the 1980s as different social participants joined the struggle, including service users, family members, health professionals and society. These social participants joined the discussions and consolidated the struggle for humanized mental health care (Simões, Fernandes, & Aiello-Vaisberg, 2013). …”
Section: Palavras-chave: Escala De Atitudes; Saúde Mental; Precisão Dmentioning
confidence: 99%
“…O tratamento deixou de ser centrado na hospitalização para buscar a melhoria da qualidade de vida do usuário, com ênfase em práticas integrais e de promoção à saúde, buscando a autonomia e a cidadania dos pacientes (Simões, Fernandes, & Aiello-Vaisberg, 2013).…”
Section: Apoio Matricial E Atenção Básicaunclassified